Uzawa's Preference Axioms - Gordon, E. (Review of Economic Studies, 1971)
Journal Article Uzawa's Preference Axioms Get access E. Gordon E. Gordon Claremont Graduate School Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 3, July 1971, Pages 319–329, https://doi.org/10.2307/2296385 Published: 01 July 1971